2014
DOI: 10.5424/fs/2014232-03514
|View full text |Cite
|
Sign up to set email alerts
|

Heathlands, fire and grazing. A palaeoenvironmental view of Las Hurdes (Cáceres, Spain) history during the last 1200 years

Abstract: Aim of study. The diachronic study of vegetation change through palynological analysis of sedimentary deposits is an essential tool both to design sound strategies on landscape  management and to understand its anthropogenic dynamics.Area of study. La Meseguera mire (Ladrillar, Cáceres, Spain) is located in the Hurdes region in the western part of Iberian Central System and started to develop at the beginning of the Islamic period (ca. 770 cal AD), in an area widely dominated by heathland.  Material and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…These facts fit current fire activity in Mediterranean ecosystems, characterized by its erratic dynamics at spatial and temporal scales depending on biomass burning, fuel availability, settlement patterns, and land use strategies (Pausas et al, ; Vannière et al, , ; Marlon et al, ). Although fire history of the Mediterranean basin seems to be mediated mainly by the variability of the Holocene climate (Turner et al, ; Pyne, ; Vannière et al, ; Marlon et al, ), several paleofire reconstructions from the Iberian Peninsula have shown that sometimes the inherent dynamics of vegetation and human activities may eclipse the climate regulating role on the fire regime, especially during the late Holocene (Gil‐Romera et al, ; Connor et al, ; Morales‐Molino et al, , ; Abel‐Schaad et al, ; Morales‐Molino et al, ). For instance, in southeastern Iberian Peninsula, it has been shown that the expansion of P. pinaster forests during the mid‐Holocene likewise produced significant changes in the fire regime independently of regional climate variability (Carrión & van Geel, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These facts fit current fire activity in Mediterranean ecosystems, characterized by its erratic dynamics at spatial and temporal scales depending on biomass burning, fuel availability, settlement patterns, and land use strategies (Pausas et al, ; Vannière et al, , ; Marlon et al, ). Although fire history of the Mediterranean basin seems to be mediated mainly by the variability of the Holocene climate (Turner et al, ; Pyne, ; Vannière et al, ; Marlon et al, ), several paleofire reconstructions from the Iberian Peninsula have shown that sometimes the inherent dynamics of vegetation and human activities may eclipse the climate regulating role on the fire regime, especially during the late Holocene (Gil‐Romera et al, ; Connor et al, ; Morales‐Molino et al, , ; Abel‐Schaad et al, ; Morales‐Molino et al, ). For instance, in southeastern Iberian Peninsula, it has been shown that the expansion of P. pinaster forests during the mid‐Holocene likewise produced significant changes in the fire regime independently of regional climate variability (Carrión & van Geel, ).…”
Section: Discussionmentioning
confidence: 99%
“…year bp ; Vannière et al, ; Burjachs & Expósito, ). In contrast, during the last 3,000 years, fire regime has been essentially mediated by anthropic activity (Abel‐Schaad et al, ; López‐Sáez et al, ; Morales‐Molino et al, ; Vannière et al, ). Human impact and fire regime in the Mediterranean region have been analyzed by many research works in the last decades (Colombaroli et al, , ; Vannière et al, , , ; Connor et al, ; Leys et al, , ; Doyen et al, ), demonstrating that fire was a key factor in mountain ecosystems management since the Neolithic with the aim of creating open spaces in forests for both agricultural and livestock activities (Colombaroli et al, ; Lillios et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the distribution and density of pine trees have been strongly affected by anthropogenic activities over recent centuries ( Ruiz-Benito, Gomez-Aparicio & Zavala, 2012 ; Lopez-Merino et al, 2014 ), resulting in local extinction, as well as the connectivity and fragmentation of pine tree coverover time. For example, Abel-Scaad, Lopez-Saez & Pulido (2014) showed that pine trees locally disappeared from the Central Iberian System during the middle ages. In contrast, these areas were 80% afforested with pines trees over the 1940–1950 period.…”
Section: Discussionmentioning
confidence: 99%
“…Palynological research in the Central System indicates that from the Iron Age to the Early Middle Ages, anthropic activities were still sporadic and mainly located in the lowlands, but from the Feudal Period onwards, when La Mesta transhumance system took place, they spread into the high mountains (López-Sáez et al, 2014). Livestock herds were transhumant, moving to and from pastures in the kingdom according to the season through protected and defined cattle trials (Abel-Schaad and López-Sáez, 2012; Abel-Schaad et al, 2014; López-Merino et al, 2009; López-Sáez et al, 2009). The main tracks ( Cañadas Reales ) took most of large herds over long distances on well-defined itineraries, joining wintering areas in the South with summering areas in the North.…”
Section: Discussionmentioning
confidence: 99%